Motor skills assessment to predict table tennis performance? - A longitudinal study - Faber, I. R.; Oosterveld, F. G. J.; Elferink Gemser, M. T.; Nijhuis-van der Sanden, M. W. G. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Talent development programs in table tennis are used to help young children, who have been identified as high potentials, to develop into elite players. Selecting young players for these programs remains extremely difficult, because of the unpredictability of long-term success. A motor skills assessment (MSA) could be helpful in talent development by estimating essential perceptuo-motor skills of young players, which are considered requisite to develop excellent technical and tactical qualities (Vandorpe et al. 2012). The Netherlands Table Tennis Association uses a MSA in their talent development program. This MSA has proven reproducibility and good prospects for validity (Faber 2013a, 2013b). However, the predictive value is still unknown. This study aimed to investigate the predictive value of the MSA for table tennis competition outcomes in a longitudinal design. Methods: In total, 39 young table tennis competitive players (7-11 years) were tested using the MSA. The MSA consists of eight test items measuring table tennis specific skills under varying conditions: sprint, agility, vertical jump, speed while dribbling, aiming at target, ball skills, throwing a ball and eye-hand coordination (Faber 2013a, 2013b). Competition results were monitored 2.5 years (five consecutive competition periods of 6 months). An Generalized Estimating Equations analysis was conducted to explore univariate and multivariate models for the MSA items to predict longitudinal competition results. Test age, sex and training experience were investigated as covariates. Results: All MSA test items but one (agility), test age, and training experience were significant predictors of competition outcome in univariate models (p<0.001). The best fitting model included the test items: sprint, throwing a ball, and eye-hand coordination. These test items explained 46% of the variance of the longitudinal competition results. Test age was included as covariate. Discussion: The results confirm that assessing perceptuo-motor skills is meaningful in a talent development program. The test items included in the best fitting model cover essential performance characteristics: speed, agility, anticipation and ball control. However, it must be emphasized that for a fair prediction of successful performance, multidimensional performance characteristics should be taken into account (Elferink-Gemser et al. 2011).